2004
DOI: 10.1074/jbc.m403440200
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts in Higher Plant Cells

Abstract: A large body of evidence from the past decade supports the existence of functional microdomains in membranes of animal and yeast cells, which play important roles in protein sorting, signal transduction, or infection by pathogens. They are based on the dynamic clustering of sphingolipids and cholesterol or ergosterol and are characterized by their insolubility, at low temperature, in nonionic detergents. Here we show that similar microdomains also exist in plant plasma membrane isolated from both tobacco leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
119
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 423 publications
(134 citation statements)
references
References 57 publications
10
119
0
2
Order By: Relevance
“…Consistent with this idea of multiple PM microdomains recruiting different sets of proteins, is the observation that lipid rafts isolated from healthy tobacco were capable of recruiting aquaporins, whereas both tested barley aquaporin isoforms, known to be expressed in the leaf epidermis, were excluded from the Bgh-triggered microdomain (ref. 22, this study, and Fig. 5).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Consistent with this idea of multiple PM microdomains recruiting different sets of proteins, is the observation that lipid rafts isolated from healthy tobacco were capable of recruiting aquaporins, whereas both tested barley aquaporin isoforms, known to be expressed in the leaf epidermis, were excluded from the Bgh-triggered microdomain (ref. 22, this study, and Fig. 5).…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, lack of FRAP in the Bgh-triggered microdomain is also reminiscent of lipid rafts in animal cells (20,21). Although very little is known about lipid rafts in plants, biochemical evidence for the existence of lipid raft-mediated compartmentalization of PM proteins has been recently obtained by analysis of PMs derived from healthy tobacco (22). These lipid rafts were greatly enriched in glycosylceramide and a mixture of plant sterols (stigmasterol, sitosterol, 24-methylcholesterol, and cholesterol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent experiments show that the Rac GTPase regulates the Rboh enzymatic activity by direct interaction (unpublished results). In tobacco, Rac GTPase and Rboh have been shown to be colocalized in lipid rafts at PM (43). The Rboh-mediated ROS are most likely to be used to polymerize monolignols in the cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cytosolic b-CAs have been found associated with the plasma membranes of several plant species (Utsunomiya and Muto, 1993;Santoni et al, 1998;Kawamura and Uemura, 2003;Alexandersson et al, 2004;Mongrand et al, 2004;Benschop et al, 2007;Mitra et al, 2007), and AtbCA4 specifically localizes to Arabidopsis cell membranes (Fabre et al, 2007). Mongrand et al (2004) showed that tobacco plasma membrane lipid rafts were enriched in a cytosolic b-CA and an aquaporin, NtAQP1, which has CO 2 transport activity (Uehlein et al, 2003) and decreases the resistance of the envelope to CO 2 (Uehlein et al, 2008). b-CA has also been implicated as a factor aiding the conductance of CO 2 through the leaf (Cowan, 1986).…”
Section: F Pringlei Ca2 Encodes a Cytosolic Enzymementioning
confidence: 99%